Hubungan antara Penerimaan Sosial dan Ketidakpuasan Penampilan Ideal pada Mahasiswa Dampak Standar Kecantikan Media Sosial Tiktok - Ari Yanti; Annisa Fitriani; Indah Dwi Cahya Izzati (SENTRI: Jurnal Riset Ilmiah, 2026)
Social media, particularly TikTok, plays a major role in shaping idealized beauty standards through intense and repetitive visual content. Continuous exposure to unrealistic ideals (e.g., slim body shape, fair skin, and “proportional” facial features) may encourage social comparison and contribute to negative body evaluation, leading to dissatisfaction with one’s ideal appearance. This condition can affect not only intrapersonal well-being but also interpersonal functioning, especially the way students perceive their social acceptance within peer and academic environments. This study aimed to examine the relationship between ideal appearance dissatisfaction and perceived social acceptance among university students who actively use TikTok. A quantitative approach with a survey design was employed. Participants were 150 university students aged 18–25 years who reported active TikTok use. Data were collected using a 50-item Likert-scale questionnaire measuring ideal appearance dissatisfaction and social acceptance. Descriptive and inferential statistical analyses were conducted using SPSS. The Pearson correlation analysis revealed a significant and strong relationship between ideal appearance dissatisfaction and perceived social acceptance (r = 0.624, p = 0.000 < 0.05). The findings indicate that higher levels of dissatisfaction with ideal appearance are associated with lower levels of perceived social acceptance among students. These results underline the importance of strengthening self-acceptance, improving media literacy, and promoting responsible TikTok use to reduce maladaptive social comparison and support students’ mental health and social functioning. Future interventions may focus on psychoeducation and campus-based counseling programs that encourage healthy body image and adaptive coping strategies in the digital era.